Thermal Time Model for Egyptian Broomrape (Phelipanche aegyptiaca) Parasitism Dynamics in Carrot (Daucus carota L.): Field Validation - Cochavi, Amnon; Rubin, Baruch; Achdari, Guy; Eizenberg, Hanan (Frontiers in Plant Science, 2016)
Carrot, a highly profitable crop in Israel, is severely damaged by Phelipanche aegyptiaca ‎parasitism. Herbicides can effectively control the parasite and prevent damage, but for ‎optimal results, knowledge about the soil-subsurface phenological stage of the parasite is ‎essential. Parasitism dynamics models have been successfully developed for the parasites P. ‎aegyptiaca, Orobanche cumana and O. minor in the summer crops, tomato, sunflower and ‎red clover, respectively. However, these models, which are based on a linear relationship ‎between thermal time and the parasitism dynamics, may not necessarily be directly ‎applicable to the P. aegyptiaca-carrot system. The objective of the current study was to ‎develop a thermal time model to predict the effect of P. aegyptiaca parasitism dynamics on ‎carrot growth. For development and validation of the models, data was collected from a ‎temperature-controlled growth experiment and from 13 plots naturally infested with P. ‎aegyptiaca in commercial carrot fields. Our results revealed that P. aegyptiaca development ‎is related to soil temperature. Moreover, unlike P. aegyptiaca parasitism in sunflower and ‎tomato, which could be predicted both a linear model, P. aegyptiaca parasitism dynamics ‎on carrot roots required a nonlinear model, due to the wider range of growth temperatures of ‎both the carrot and the parasite. Hence, two different nonlinear models were developed for ‎optimizing the prediction of P. aegyptiaca parasitism dynamics. Both models, a beta ‎function model and combined model composed of a beta function and a sigmoid curve, were ‎able to predict first P. aegyptiaca attachment. However, overall P. aegyptiaca dynamics was ‎described more accurately by the combined model (RMSE =14.58 and 10.79, respectively). ‎The results of this study will complement previous studies on P. aegyptiaca management by ‎herbicides to facilitate optimal carrot growth and handling in fields infested with P. ‎aegyptiaca. ‎